Inovasi untuk Keberlanjutan Usaha Kuliner - Yuhendri L V (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
This research aims to describe the innovations made by sanjai entrepreneurs for the sustainability of culinary businesses in Bukittinggi City. The research approach is qualitative research with a type of phenomenology research. Sampling techniques use snowball sampling. The key informant is sanjai entrepreneurs. Data collection techniques use in-depth interviews, participation observations, and documentation. Data analysis techniques use miles, huberman, & saldana qualitative research data analysis processes. The results showed that the source of entrepreneurial innovation ideas was obtained from watching videos on Youtube, modeling similar businesses, modeling other different businesses, the result of self-thought, and seeing business products at exhibitions. Forms of innovation carried out by sanjai entrepreneurs are product innovation, technology innovation, and service innovation. The impact of innovation on business sustainability is that products are favored by consumers, consumers increase, revenue increase, profits increase, businesses survive and are sustainable.  The results of the research can be used as a reference for culinary entrepreneurs in innovating for the sustainability of culinary businesses.